Political Order and Nomadic Life in Iran: From the Afsharid Period to the End of the Qajar Dynasty - Shahram Gholami; Siavash Gholipour (پژوهش های تاریخی)
Abstract This article explored the impact of political order on nomadic lifestyles from the Afsharid period to the end of the Qajar dynasty. The central question of this research was to clarify the factors contributing to fluctuations in nomadic life over nearly two centuries. By the end of the 18th century, nomadic lifestyles had significantly increased, whereas in the final decades of the 19th century—specifically, at the close of the Qajar era—they declined in favor of sedentary living. The primary inquiry examined whether the dynamics of nomadism during this period were predominantly influenced by geographical conditions or shaped by the political system. The methodology utilized in this study was descriptive-analytical, employing documentary data collection techniques. The findings suggested that, although the nomadic lifestyle might initially seem to be a conscious adaptation to ecological conditions, its expansion during this period was largely driven by political and security concerns. The results indicated that from the Afsharid period through the early Qajar rule, the rise in nomadism was a response to insecurity and governmental policies. In contrast, the final decades of the 19th century saw relative political stability, bureaucratic expansion, and integration into the global economic system, which accelerated the transition from nomadic to sedentary lifestyles. Introduction In ancient times, agriculture was the cornerstone of Iranian life. However, with the invasions by Arab nomads, Turks, and Mongols, agriculture gradually lost its prominent status, leading to nomadism becoming the traditional way of life for many Iranians during the Middle Ages. Some scholars attributed the prosperity of nomadic lifestyles to their adaptability to environmental conditions and seasonal changes. They argued that the cold highlands and tropical plains surrounding the Iranian plateau provided an ideal environment for this mode of living, allowing people to efficiently utilize water and soil resources, ultimately resulting in economic prosperity. Conversely, another group contended that fluctuations in migration patterns were primarily influenced by changes in political systems and defense relations among different human groups. This article sought to critically evaluate the role of environmental adaptability as a cause for the spread of nomadism, aligning more closely with the latter perspective. The central question guiding this inquiry was: What impact did the political system have on the nomadic way of life? Materials & Methods This research employed a descriptive-analytical approach, focusing on the period from the rise of the Afsharid dynasty to the end of the Qajar dynasty. Data collection techniques included the examination of archival documents from the National Library of Iran, internal written sources, and travelogues. Data analysis was conducted through the systematic organization of the collected information. Research Findings During the Afsharid, Zandiyeh, and early Qajar periods, alliances among nomadic tribes emerged in response to ongoing wars and insecurity. This led to a decrease in the number of settled villagers and an increase in nomadic groups. The resulting insecurity prompted a transformation in village morphology, evolving into more complex structures resembling castles. Nomadism offered several advantages, including military strength, security, and a sense of freedom. The pride associated with a nomadic lifestyle in contrast to that of townspeople and villagers stemmed from this relatively safer and freer existence. However, this did not translate into improved economic conditions; nomadic economies were primarily subsistence-based with little surplus for market supply. The lack of a unified warehouse and market further exacerbated these challenges. Additionally, nomadic practices often misaligned with the optimal productivity of water and soil resources. Agricultural capacities within nomadic territories were diminished and livestock frequently damaged crops. As a result, much of the fertile agricultural land fell into disrepair and neglect. The establishment of a new political system during the Qajar period—marked by an expanding administrative bureaucracy, relative security, and the growth of foreign trade—facilitated the settlement of nomads in certain regions. The Qajar government delegated some administrative responsibilities to nomadic leaders and encouraged urban settlement among their communities. The expansion of global trade in the mid-19th century integrated some nomadic economies into the global capitalist framework, prompting a shift from traditional nomadism to settled agriculture. Many nomads found it more economically viable to cultivate cash crops, such as tobacco, leading some to settle in villages at the initiative of their leaders. In certain areas, nomadic leaders' acquisition of communal lands contributed to the emergence of feudal societies. By the end of the Qajar period, the settlement of tribal leaders and weakening of government authority resulted in ethnic and tribal conflicts spilling into urban areas, causing clashes and looting in some neighborhoods. These tensions intensified during the Constitutional Revolution and World War I, creating conditions that stifled commercial and industrial activities. As a result of these conflicts—often exacerbated by both internal factions and powerful foreign influences—many villages were devastated. The insecurity faced by settled villagers increased, leading to a decline in rural living conditions. Following the coup of 1299, the re-establishment of central government authority and heightened pressure to collect back taxes during the ensuing chaos led to rising dissatisfaction. Some settlers began to view migration as a potential solution. Overall, political instability caused many individuals to flee, intensifying migration. Additionally, the dominance of a nomadic system hindered the development of agricultural productivity and the growth of urban and commercial communities. Discussion of Results & Conclusion The stability of the government and continuity of the political system could foster a sense of unity among the populace. In contrast, insecurity, ongoing conflicts among power claimants, and tax pressures had exacerbated migration, leading to mass exoduses among villagers. As a result, the people of Iran and the broader Middle East frequently oscillated between migration and settlement. Contrary to popular belief, the choice of a nomadic lifestyle was not solely driven by its economic advantages over sedentary living. Factors like freedom, independence, and the ability to defend oneself—especially during periods of political unrest—were often prioritized. There was insufficient evidence to suggest that nomads experienced greater prosperity than their settled counterparts. Moreover, in a nomadic lifestyle—whether focused solely on herding or involving a mixed approach of herding and agriculture—the optimal exploitation of natural resources was often unattainable. As a consequence, general economic prosperity, surplus production, and wealth accumulation remained largely elusive for nomadic communities.